2021
DOI: 10.3390/molecules26144183
|View full text |Cite
|
Sign up to set email alerts
|

GC-MS Metabolic Profile and α-Glucosidase-, α-Amylase-, Lipase-, and Acetylcholinesterase-Inhibitory Activities of Eight Peach Varieties

Abstract: The inhibition of certain digestive enzymes by target food matrices represents a new approach in the treatment of socially significant diseases. Proving the ability of fruits to inhibit such enzymes can support the inclusion of specific varieties in the daily diets of patients with diabetes, obesity, Alzheimer’s disease, etc., providing them with much more than just valuable micro- and macromolecules. The current study aimed atidentifying and comparing the GC-MS metabolic profiles of eight peach varieties (“Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 100 publications
(129 reference statements)
1
9
1
Order By: Relevance
“…Chen et al [ 36 ] also showed that chingiitannin A from the unripe fruit of Rubus chingii Hu had the highest inhibitory activities against α-amylase and α-glucosidase, and had a reversible and noncompetitive mode of inhibition. Mihaylova et al [ 37 ] found that crude polyphenol extracts from eight peach varieties had no inhibitory effect on α-amylase, but the TPPs identified in our study inhibit both α-amylase and α-glucosidase, via competitive reversible inhibition and noncompetitive reversible inhibition. In addition, the EC 50 of TPPs to α-amylase was only 0.26 mg/mL, making it potentially useful for the control of blood sugar.…”
Section: Discussioncontrasting
confidence: 45%
“…Chen et al [ 36 ] also showed that chingiitannin A from the unripe fruit of Rubus chingii Hu had the highest inhibitory activities against α-amylase and α-glucosidase, and had a reversible and noncompetitive mode of inhibition. Mihaylova et al [ 37 ] found that crude polyphenol extracts from eight peach varieties had no inhibitory effect on α-amylase, but the TPPs identified in our study inhibit both α-amylase and α-glucosidase, via competitive reversible inhibition and noncompetitive reversible inhibition. In addition, the EC 50 of TPPs to α-amylase was only 0.26 mg/mL, making it potentially useful for the control of blood sugar.…”
Section: Discussioncontrasting
confidence: 45%
“…The early season fruits were quite similar to the late season and to the mid-season, and in reverse. Moreover, when clustering the metabolites in polar fractions (phenolic acids, amino acids, organic acids, sugar alcohols, carbohydrates, and saturated and unsaturated fatty acids [57]), different phytochemical similarities were reported.…”
Section: Principal Component Analysis (Pca) and Hierarchical Cluster Analysis (Hca) Of Gc-ms Datamentioning
confidence: 99%
“…Polyphenols are the most pervasive bioactive compounds found in agroindustry byproducts [10,11], various fruits [12,13], seeds [14], cereals [15], nuts [16], vegetables [17], tea [18,19], coffee [20], etc. These compounds are a group of secondary metabolites derived from phenylalanine, and they own one or more phenolic rings with one or several bound hydroxyl groups.…”
Section: Introductionmentioning
confidence: 99%